Are Profitability and Leverage Able to Predict the Risk of Financial Distress? - Mulyadi, Mulyadi; Meythi, Meythi; Martusa, Riki; Rapina, Rapina (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
The performance of the organization from a financial perspective plays a crucial role in attracting investment. Whenever this profitability indicator is put in the context of making an investment, the signaling theory arises where information about the firm’s activities is provided to affect an investment decision. The goal of this study is to observe profitability and leverage affect financial distress. The population is manufacturing enterprises registered on the Indonesia Stock Exchange between 2018 and 2022. Testing uses the SPSS statistical test tool with logistic regression. Profitability can predict the risk of financial distress. The risk of financial distress can be reduced by increasing profitability. Meanwhile, Leverage does not yet provide a definite reflection for predicting the risk of financial distress. Optimizing profits is the main thing in reducing the risk of financial distress. This will also have an impact on business continuity and not experiencing bankruptcy. The novelty of this study is that the indicator of financial distress is estimated by six consecutive years of negative earnings per share.